Agricultural policy in disarray: Volumes 1 and 2 - Smith, Vincent H.; Glauber, Joseph W.; Goodwin, Barry K. (American Enterprise Institute, 2018)
This page links to volume I and II of the 2018 publication, Agricultural policy in disarray. Previously, the volumes were separated on the AEI website.